Partial factors in modelling of steel structures reliability according to Eurocodes = Współczynniki częściowe w eurokodowym modelu niezawodności konstrukcji stalowych - Stachura, Zbigniew; Giżejowski, Marian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Problems associated with the estimation of partial factors for structural systems, subsystems and buckling of individual elements are dealt with in this paper. Aspects related to resistance factors for the section resistance and member resistance are in particular referred to. The Eurocode?s approach of resistance partial factor calibration assisted by experimental data for subframe systems is also summarized.
Keywords: kalibracja współczynników częściowych; model nośności; nośność obliczeniowa; współczynnik wyboczenia; calibration of partial factors; resistance model; partial resistance factor; design resistance; buckling reduction factor